Virion-mediated transfer of SV40 epigenetic information - Milavetz, Barry (Landes Bioscience, 2012)
In eukaryotes, epigenetic information can be encoded in parental cells through modification of histones and subsequently passed on to daughter cells in a process known as transgenerational epigenetic regulation. Simian Virus 40 (SV40) is a well-characterized virus whose small circular DNA genome is organized into chromatin and, as a consequence, undergoes many of the same biological processes observed in cellular chromatin. In order to determine whether SV40 is capable of transgenerational epigenetic regulation, we have analyzed SV40 chromatin from minichromosomes and virions for the presence of modified histones using various ChIP techniques and correlated these modifications with specific biological effects on the SV40 life cycle. Our results demonstrate that, like its cellular counterpart, SV40 chromatin is capable of passing biologically relevant transgenerational epigenetic information between infections.